2021
DOI: 10.1371/journal.pone.0251906
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity among pregnant women and associated factors in Ethiopia: Systematic review and meta-analysis

Abstract: Backgrounds Pregnancy related complications are major causes of maternal morbidity and mortality worldwide. Diversified food consumption is essential to produce hormones during pregnancy and it reduced complications. In Ethiopia, many researchers were investigated about the proportion of pregnant women with dietary diversity and its determinant factors. However, those studies are inconsistent and fragmented. Therefore, the aim of this study was to estimate the pooled proportion of pregnant women with dietary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 43 publications
3
27
1
2
Order By: Relevance
“…This finding is almost consistent with the study done in Bale zone [ 10 ], Northeast Ethiopia [ 24 ], Aksum Tigray [ 25 ]East Gojam Zone [ 6 ], A systematic review and meta-analysis finding of Ethiopia [ 26 , 27 ], and Southern Ethiopia [ 1 ]. All studies have similar sociodemographic, socioeconomic, and seasonal variations characteristics might be the possible reason for similarities.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is almost consistent with the study done in Bale zone [ 10 ], Northeast Ethiopia [ 24 ], Aksum Tigray [ 25 ]East Gojam Zone [ 6 ], A systematic review and meta-analysis finding of Ethiopia [ 26 , 27 ], and Southern Ethiopia [ 1 ]. All studies have similar sociodemographic, socioeconomic, and seasonal variations characteristics might be the possible reason for similarities.…”
Section: Discussionsupporting
confidence: 90%
“…This study found no statistically significant link between adequate dietary diversity intake and certain demographic factors (mothers' age, religion, husband education, and husband occupation). This finding is similar to one based on an Ethiopian systematic review [ 1 ]. However, mothers who earn their own money have a better chance of eating a diverse diet than mothers who do not.…”
Section: Discussionsupporting
confidence: 90%
“…Our study's proportion of adequately diverse dietary intake was lower than figures from South Africa, Kenya, Ghana, and Pakistan, which were 25 percent, 61 percent, 46 percent, and 94 percent, respectively [ 26 – 29 ]. Similarly, the finding of this study was lower than the 41 percent obtained by a systematic review of studies conducted in Ethiopia, and the 24.7 percent obtained by another community-based study conducted in the Gamo zone, Kucha district [ 1 , 30 ]. This is because the study was conducted in a rural area, where mothers may have limited access to information and may adhere to traditional dietary intake practices.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…According to some studies conducted in the country, adequate dietary diversity among pregnant women varies within the country ranging from 12.8% in the Oromia region to 61.2% in the Tigray region [ 26 31 ]. Educational status of the mother, monthly household income, livestock ownership, women who received emotional support from their husbands, wealth index, women who engaged in shopping, and nutrition information are all factors that influence pregnant women's dietary variety practices [ 26 29 ]. However, research has scarcely investigated women's empowerment and women's employment in dietary diversity practice during pregnancy in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%